"Free Thoughts on Religion, the Church, and National Happiness" Bernarda Mandeville`a jako lekcja anatomii natury ludzkiej w praktyce = "Free Thoughts on Religion, the Church, and National Happiness" by Bernard Mandeville as a human nature anatomy lesson in practice - Droś, Agnieszka (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article attempts to present Bernard Mandeville`s lessons on the anatomy of human nature in practice, i.e. the practical application of knowledge about human passions by clever clergymen-politicians. Based mainly on "Free Thoughts on Religion, the Church, and National Happiness", it has been proven that religion in the views of the author of this work is part of a system that is to keep society together by basing to the fear of an invisible power. At the same time, religion becomes an instrument used for constant abuse, struggle for power and material goods by clergy who skillfully manipulate human weaknesses.
Keywords: Mandeville, Bernard de (1670-1733); "Free Thoughts on Religion, the Church, and National Happiness"; religion; anatomy of human nature; English enlightenment; religia; anatomia natury ludzkiej; oświecenie angielskie